Geriatric Oncology OSCE: Using Geriatric Assessment Tools to Guide Patient Treatment Decisions - Kathryn Denson; Gabriel Manzi; Patrick Foy; Thomas Giever; Judith Rehm (Association of American Medical Colleges, 2014)
Abstract Introduction Fellowship Programs must soon comply with the ACGME's Next Accreditation System (NAS) Milestone performance tracking and reporting requirement and consider Entrustable Professional Activities (EPAs) to measure learner performance. At the Medical College of Wisconsin (MCW), geriatricians and oncologists worked together to create and implement a geriatric oncology educational OSCE for oncology fellows. Key curriculum content gaps (geriatric cognitive, functional, and psychosocial assessment) were identified through oncology fellow and faculty knowledge/performance gaps on a needs assessment survey/pretest. Methods Curriculum content, intended to introduce geriatric assessment tools, was delivered using an initial one hour didactic presentation/demonstration session. The second session, one week later, was a two case OSCE session followed by a debrief session, designed to give learners practice using the tools with standardized patients as both an educational/assessment method. Fellows assessed their competency level in those initial EPAs both pre- and postOSCE curriculum intervention (1 = cannot perform, 5 = teach others). This MedEdPORTAL submission contains all materials for the geriatric oncology OSCE regarding geriatric oncology patient assessment, including materials for the initial didactic/demonstration session, standardized patient training session, two sets of OSCE station educational materials, debrief session, pre-/postEPA surveys and session evaluation form. There are four geriatrics assessment tools used, which are included as attachments. Results Results of the post OSCE session evaluations showed fellows (N = 9) rating "The OSCEs were an effective method for increasing my confidence and skills in caring for elderly patients" and "The OSCE cases were believable and applicable to clinical practice" with means of 4.6 and 4.8 (1 = poor, 5 = excellent), respectively. Session strengths included, "This is a great reminder of the need to do functional and cognitive assessment," "Very realistic patient cases and scenarios," and "Discussion session at the end solidified it all." Pre- and postEPA ratings revealed a shift to competence. The EPA item, "I can apply geriatric assessment tools to better prognosticate/understand treatment risk and benefit in elderly cancer patients" shifted from a mean of 2.5 to 5.0 (1 = cannot perform, 5 = teach others). The item, "I can identify risks and benefit of cancer treatment versus non-treatment outcomes for elderly patients (life expectancy, treatment side effects, complications, quality of life) showed pre- to posttest change from a mean of 3.2 to 4.8. Discussion This curriculum was successfully implemented in the oncology fellowship core curriculum but could also be implemented with other levels and types of learners (residents, medical students). Resource limitations may include space and standardized patients.